Outcome of vaginal sildinafil in assisted reproductive technology cycles - Kapoor, Avnika; Sharma, Garima; Bakshi, Rita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The present study assessed the role of sildenafil in endometrial blood flow and successful pregnancy in IVF done in surrogate mothers. Methods: In the present study surrogate mothers were included. Thirty patients were randomized to receive sildenafil 25 mg thrice a day vaginally in addition to standard drugs and technique and another 30 were not given sildenafil. Results: Mean age, anthropometry, duration of infertility and pre-treatment endometrial thickness was similar in the two study groups. After treatment completion, it was observed that the endometrial pattern in ultrasound was similar in the two study groups (p value=0.58). Heterogenic endometrial pattern was observed in 6.7% of the Sildenafil patients and 3.3% in the control patients, while echogenic pattern was seen in 10% of the sildenafil patients and 6.7% of the control patients. Similarly, endometrial thickness was 10.2±1.7 and 9.7±1.8 mm in sildenafil and control group respectively, p value=0.62. Using doppler ultrasound, uterine artery PI was significantly lower in Sildenafil group patients as compared to control group patients. Similarly, we found uterine artery RI was also significantly lower in the Sildenafil group patients as compared to control group patients. We followed the patients and found that clinical pregnancy rate was significantly higher among Sildenafil group (60%) as compared to control group (26.6%), p value<0.05. Conclusions: Vaginal sildenafil resulted in significantly higher pregnancy rates in our study population. The uterine artery PI and RI were significantly lower in patients taking sildenafil.